Role and place of specialist of physical rehabilitation in the population health care system. - Prystupa Yvgenij Nikodimovich; Vovkanych Andrej Stepanovich (Kharkov National Pedagogical University, 2011)
The state of health of Ukraine population has been examined according with indices of expected life duration and expected health life duration; efficiency of prophylactic and health-related technologies in elimination of most main reasons of loss of healthy years of life has been shown; main problems of physical rehabilitation's development as of branch of health care have been defined (in particular, absence of adequate possibilities of employment of specialists of physical rehabilitation). Analysis of publications dealing with problems of health care and improvement of population`s quality of life in national and foreign periodic and in Internet has been presented.